Increase of DNA damage and alteration of the DNA damage response in myelodysplastic syndromes and acute myeloid leukemias - Popp, Henning; Naumann, Nicole; Brendel, Susanne; Henzler, Thomas; Weiß, Christel; Hofmann, Wolf-Karsten; Fabarius, Alice (Leukemia research, 2017)
Increased DNA damage and alteration of the DNA damage response (DDR) are critical features of genetic instability presumably implicated in pathogenesis of myelodysplastic syndromes (MDS) and acute myeloid leukemias (AML). We used immunofluorescence staining of γH2AX and 53BP1 for analyzing DNA double-strand breaks (DSB) in MDS and AML cell lines, in CD34+ selected cells of normal and MDS bone marrow (including three cases of chronic myelomonocytic leukemias) and in blasts of AML bone marrow. In addition, we screened for activation of the DDR by immunoblotting of p-ATM, p-ATR, p-CHK1, p-CHK2 and p-TP53. As compared to γH2AX foci levels in normal bone marrow samples (0.2 focus per CD34+ cell±0.0; mean±standard error of mean), increased levels of γH2AX foci were detected in 16/16 MDS bone marrow samples (2.8 foci per CD34+ cell±0.5), 18/18 AML bone marrow samples (5.5 foci per blast±0.5), 1/1 MDS cell line (6.4 foci per cell) and 6/6 AML cell lines (12.0 foci per cell±0.6). γH2AX and 53BP1 co-localized in all tested samples forming diffuse, clustered and marginal patterns. Further, DDR proteins were expressed heterogeneously suggesting impairment of the DDR. In summary, our results provide evidence for a continuous increase of DSB across the spectrum from MDS to AML in conjunction with an impaired DDR. Co-localization of γH2AX and 53BP1 indicates promotion of (in)effective nonhomologous end-joining repair mechanisms at sites of DSB. Moreover, γH2AX/53BP1 foci distribution presumably reveals a non-random spatial organization of the genome in MDS and AML.